1982
DOI: 10.1246/bcsj.55.55
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of the Tris(2,2′-bipyridine)ruthenium(II) Ion with Poly(p-styrenesulfonate)

Abstract: The interactions of tris(2,2′-bipyridine)ruthenium(II)([Ru(bpy)3]2+) with some polyanions have been studied by means of cation-exchange resins and the luminescence of [Ru(bpy)3]2+. In an aqueous solution of [Ru(bpy)3]2+ in the presence of sodium poly(p-styrenesulfonate)(PSS), the adsorbability of [Ru(bpy)3]2+ on the cation-exchange resins is strongly suppressed by the binding of [Ru(bpy)3]2+ to the polyanion. The relative luminescence intensity of [Ru(bpy)3]2+ in an aqueous solution is enhanced by the addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 12 publications
1
15
0
Order By: Relevance
“…40 No evidence for complex formation between the polyviologens and the ruthenium complexes could be observed, and the rates of both the forward and backward reactions taking place in the photochemical systems were not found to exceed the diffusioncontrolled limit as has been observed previously for reactions of other polyvi~logens'~~'~ and other polyelectrolytes where hydrophobic interactions are important. and BSV-S.~ They may also be similar to the strong hydrophobic interactions observed between the 2,2'-bipyridine or 1,lO-phenanthroline ligands and the phenyl group of poly(styrenesu1fonate).…”
Section: Systems Containing R~( B P Y )~ ' Asmentioning
confidence: 49%
“…40 No evidence for complex formation between the polyviologens and the ruthenium complexes could be observed, and the rates of both the forward and backward reactions taking place in the photochemical systems were not found to exceed the diffusioncontrolled limit as has been observed previously for reactions of other polyvi~logens'~~'~ and other polyelectrolytes where hydrophobic interactions are important. and BSV-S.~ They may also be similar to the strong hydrophobic interactions observed between the 2,2'-bipyridine or 1,lO-phenanthroline ligands and the phenyl group of poly(styrenesu1fonate).…”
Section: Systems Containing R~( B P Y )~ ' Asmentioning
confidence: 49%
“…However, the pH used in the present system was 3.6, and the major ionizable groups in HA were undissociated. Therefore, the binding of Ru(bpy)3 2+ and MV 2+ with HA may be due to strong cooperative binding by the interaction of aromatic rings as well as anionic electrostatic forces, as reported for the case of PVS (30).…”
Section: Resultsmentioning
confidence: 61%
“…It has been reported that neutral urea, which interacts through van der Waals and H-bonds, can also displace [Ru(bpy) 3 ] 2+ from PSS, 24 indicating the importance of non-coulombic interactions in this system. Similar behaviour was observed on addition of MgCl 2 ( Fig.…”
Section: Dppz]mentioning
confidence: 92%
“…The increases in luminescence intensity and lifetime observed when [Ru(bpy) 3 ] 2+ interacts with PSS 24,25,27 are attributed to binding in a less polar environment via a combination of electrostatic and hydrophobic interactions, lower local water activity, and reduced oxygen quenching (see below). Shielding [Ru(bpy) 3 ] 2+ from water enhances the luminescence quantum yield, 42 since the presence of water increases non-radiative decay.…”
Section: +mentioning
confidence: 99%